Implementasi manajemen risiko terintegrasi sebagai strategi peningkatan kinerja berkelanjutan pada bank umum syariah di era dinamika ekonomi digital - Sabrina, Siti Nabila Zida (Maliki Interdisciplinary Journal, 2025)
Sharia banks around the world are preparing to enter the rapidly changing digital economy. Therefore, they face new challenges and opportunities in dealing with digitalization. For sharia banks, digitalization can support the principles of sustainable sharia banking and improve operational efficiency. However, the complexity of risks, such as those related to cyber, operational, and compliance risks, is also increasing. This study aims to analyze how integrating risk management can play a role as a strategy for the sustainable growth of Islamic banks. The results of the study show that the identification, evaluation, control, and monitoring of risks through systematic risk management have a direct effect on improving the institutional sustainability of banks in the digital market.